The Struggle for Territorial Control in Colombia: An Analysis of the Dynamics of the Armed Conflict (2015)
This paper reviews the literature on the theory of armed conflict and examines its application to the insurgents´ struggle with the State for political and territorial control in Colombia during 1999-2010 -- The analysis examines three sub-periods during this period and several geographic regions to analyze the effect of varying levels of participant capability on the dynamics of the conflict, as measured by the intensity of the conflict over time -- We conclude that as long as there are asymmetries between the State and the insurgency, armed confrontation is likely to continue